Brief Report: Blockade of TANK‐Binding Kinase 1/IKKɛ Inhibits Mutant Stimulator of Interferon Genes (STING)–Mediated Inflammatory Responses in Human Peripheral Blood Mononuclear Cells. Issue 7 (5th June 2017) - Frémond, Marie‐Louise; Uggenti, Carolina; Van Eyck, Lien; Melki, Isabelle; Bondet, Vincent; Kitabayashi, Naoki; Hertel, Christina; Hayday, Adrian; Neven, Bénédicte; Rose, Yoann; Duffy, Darragh; Crow, Yanick J.; et al.
Abstract : Objective: Gain‐of‐function mutations in TMEM173, encoding the stimulator of interferon (IFN) genes (STING) protein, underlie a novel type I interferonopathy that is minimally responsive to conventional immunosuppressive therapies and associated with high frequency of childhood morbidity and mortality. STING gain‐of‐function causes constitutive oversecretion of IFN. This study was undertaken to determine the effects of a TANK‐binding kinase 1 (TBK‐1)/IKKɛ inhibitor (BX795) on secretion and signaling of IFN in primary peripheral blood mononuclear cells (PBMCs) from patients with mutations in STING. Methods: PBMCs from 4 patients with STING‐associated disease were treated with BX795. The effect of BX795 on IFN pathways was assessed by Western blotting and an IFNβ reporter assay, as well as by quantification of IFNα in cell lysates, staining for STAT‐1 phosphorylation, and measurement of IFN‐stimulated gene (ISG) messenger RNA (mRNA) expression. Results: Treatment of PBMCs with BX795 inhibited the phosphorylation of IFN regulatory factor 3 and IFNβ promoter activity induced in HEK 293T cells by cyclic GMP‐AMP or by genetic activation of STING. In vitro exposure to BX795 inhibited IFNα production in PBMCs of patients with STING‐associated disease without affecting cell survival. In addition, BX795 decreased STAT‐1 phosphorylation and ISG mRNA expression independent of IFNα blockade. Conclusion: These findings demonstrate the effect of BX795 on reducing type I IFN production and IFN signaling in cells from patients with gain‐of‐function mutations in STING. A combined inhibition of TBK‐1 and IKKɛ therefore holds potential for the treatment of patients carrying STING mutations, and may also be relevant in other type I interferonopathies.